math, Algebra

4(3x-2) -5(x+1)=6-(4x-3)
Posted Date: 8/23/2012 7:38:40 PM | Location : United States







Related Discussions:- math, Assignment Help, Ask Question on math, Get Answer, Expert's Help, math Discussions

Write discussion on math
Your posts are moderated
Related Questions
let x,y,z be the complex number such that x+y+z=2,x^2+y^2+z^=3,x*y*z=4,then 1/(x*y+z-1)+1/(x*z+y-1)+1/(y*z+x-1) is

can you help and is it free?

can any one help me with my geometry

i need help with my homework


I am trying to figure out this answer f(x) = -3/4x + 4. but think I am getting it all wrong



I have 4 word problem on my review that I cant figure out. Can you help me?

First, the standard form of a quadratic equation is                                   ax2 + bx + c = 0                          a ≠ 0 Here the only needs are that we have an